Influence of laptops in lifelong learning: A study of student and teacher perspectives - Nair, Radhakrishnan (2010)
This paper examines the perspectives of students and teachers on the influence of laptops in lifelong learning. The data was collected by distributing questionnaires to students in the age group of 18-20 years in the foundation year of the German University of Technology in Oman. Lecturers were also surveyed to obtain their perspective. The questionnaire had 20 multiple choice and short answer questions. Responses were anonymous. The results of this study would benefit teachers and administrators of higher education institutions aiming improvement in the effective use of laptops for lifelong learning.